Subsidizing unit donations: matches, rebates, and discounts compared - Diederich, Johannes; Eckel, Catherine C.; Epperson, Raphael; Goeschl, Timo; Grossman, Philip Johnson (AWI discussion paper series, 2020)
An influential result in the literature on charitable giving is that matching subsidies dominate rebate subsidies in raising funds. We investigate whether this result extends to 'unit donation' schemes, a popular alternative form of soliciting donations. There, the donors' choices are about the number of units of a charitable good to fund at a given unit price, rather than the amount of money to give. Comparing matches and rebates as well as simple discounts on the unit price, we find no evidence of dominance in our online experiment: The three subsidy types are equally effective overall. At a more disaggregate level, rebates lead to a higher likelihood of giving while matching and discount subsidies lead to larger donations by donors. This suggests that charities using a unit donation scheme enjoy additional degrees of freedom in choosing a subsidy type. Rebates merit additional consideration if the primary goal is to attract donors.
Keywords: Graue Literatur